2018
DOI: 10.5267/j.msl.2018.6.013
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a moderator of the relationship between work family conflict and family satisfaction

Abstract: This study examines the role of social support in the relationship between work family conflict (work to family; WFC & family to work; FWC) and family satisfaction for private sector employees. Using simple random sampling, data were collected from 260 employees from eight private companies in Terengganu, who responded to the Job Content Questionnaire, Work Family Conflict Scale and Family Satisfaction Scale. Results indicate that both WFC and FWC had significant relationships with family satisfaction. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…This finding implies that individuals experiencing WIF or FIW will consequently witness WFC which is situated in the domain specificity theory of one role domain inhibiting another role domain thus, making it unattainable to meet the demands of the latter role. Thus, buttressing the point that WFC is bi-directional Beutell, 2010;Kinnunen, Feldt, Mauno, & Rantanen, 2010;Aslam, Shumiala, Azhar, & Sadaqat, 2011;Allen, Johnson, Kiburz, & Shockley, 2013;Jamaludin, Ibrahim, & Dagang, 2018;Tsaur & Yen, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding implies that individuals experiencing WIF or FIW will consequently witness WFC which is situated in the domain specificity theory of one role domain inhibiting another role domain thus, making it unattainable to meet the demands of the latter role. Thus, buttressing the point that WFC is bi-directional Beutell, 2010;Kinnunen, Feldt, Mauno, & Rantanen, 2010;Aslam, Shumiala, Azhar, & Sadaqat, 2011;Allen, Johnson, Kiburz, & Shockley, 2013;Jamaludin, Ibrahim, & Dagang, 2018;Tsaur & Yen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Work-family interference represents the ability of workplace issues and roles to interfere with family roles and responsibilities of an individual. This dimension of the WFC has also been described as taking work home (Jamaludin, Ibrahim, & Dagang, 2018;Tsaur & Yen, 2018;Aslam, Shumiala, Azhar, & Sadaqat, 2011;Ahmad, 2008), describing the situation where the work duties of an individual are capable of creating some kind of conflict in the family domain as both demands struggle over the finite time and energy at the disposal of the individual, resulting in work-family interference that ultimately results in work-family conflict. In contrast, when there is a disturbance in the work-life of an individual as a result of fulfilling family demands, there is a creation of Family-Work Interference (FIW) .…”
Section: Wif and Fiwmentioning
confidence: 99%
“…The findings showed that family-to-work conflict was negatively correlated with family satisfaction. In another study, Jamaludin et al (2018) examined the relationship between work-family conflict and job satisfaction among employees of private companies in Malaysia. The results indicated that family-to-work conflict and work-to-family conflict had a significant negative relationship with family satisfaction.…”
Section: Empirical Review Of Work-family Conflict and Family Satisfactionmentioning
confidence: 99%
“…This indicates that when employees ensure a balance between work and family responsibilities, it enhances family satisfaction. Jamaludin et al (2018) carried out a cross-sectional survey among private-sector employees in Malaysia. The purpose of the study was to investigate the relationship between work-family conflicts and family satisfaction with a moderating role of social support.…”
Section: Empirical Review Of Work-family Conflict and Family Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation